Heritable cancer predisposition testing in pediatric cancer patients excluding retinoblastoma in a middle‐income country. Issue 11 (12th September 2022) - El Khatib, Omar; Yahya, Yasser; Mahfouz, Rami; Hamadeh, Lama; Basbous, Maya; Abboud, Miguel R.; Muwakkit, Samar; Rodriguez‐Galindo, Carlos; Jeha, Sima; Saab, Raya
Abstract: Resource‐limited settings often have financial barriers to genetic testing for heritable cancer. This retrospective study investigated the pattern of heritable cancer predisposition testing in a middle‐income country over the period 2014–2021, excluding retinoblastoma. After establishing a specific fund in 2019, rate of tests increased from 1.1% to 10.9% of new diagnoses. Most common testing was for constitutional mismatch repair deficiency (CMMRD), rhabdoid predisposition syndrome, TP53 (tumor protein 53) mutation, and hereditary cancer panel. Of 33 patients, 13 (39%) tested positive, 12 (36%) negative, and eight (24%) had variants of unknown significance. Positivity rate was 43% for a clinical phenotype and 44% for a tumor type indication.